From Experience to Loyalty: Investigating Customer Retention Drivers in Coffee Shops - Angelia Widhy; Nonot Yuliantoro; Vasco A.H. Goeltom (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The rapid expansion of the coffee shop industry in Indonesia reflects a significant transformation in consumer preferences, particularly among urban populations seeking high-quality products and engaging social experiences. While previous studies have examined the impact of product and service quality on customer loyalty, empirical research in the context of local independent coffee brands remains limited. This study aims to investigate the influence of product quality and service quality on customer loyalty in the context of TKT in Tangerang, a rapidly urbanizing region in Indonesia. Using quantitative research design, data was collected through structured questionnaires distributed to 227 respondents who are regular customers of TKT outlets in Tangerang. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the relationships among variables. The findings indicate that both product quality and service quality have a significant and positive effect on customer loyalty, with product quality emerging as the more dominant factor. These results align with the theoretical framework proposed by Zeithaml and provide further empirical validation within a local Indonesian context. The study contributes to the existing literature by contextualizing loyalty behavior in an emerging coffee market and offers practical insights for local F&B brands aiming to sustain customer retention through quality-driven strategies. Future research is recommended to incorporate mediating variables such as customer satisfaction or emotional engagement to enrich the loyalty framework in similar service settings